Participatory validation and optimization of the Triple S method for sweetpotato planting material conservation in southern Ethiopia - Hundayehu, M.C.; McEwan, M.; Namanda, S.; Low, Jan W.; Vandamme, Elke; Brouwer, R. (Walter de Gruyter GmbH, 2022)
A climate-resilient, root-based sweetpotato planting material (SPM) conservation method called “Triple S” or “Storage in Sand and Sprouting” has created timely access to sweetpotato planting material in areas with a prolonged dry season in Uganda and Tanzania. The aim of this study was to validate and optimize the Triple S method for conservation of sweetpotato planting material in dry areas of southern Ethiopia. The Triple S method was validated in four districts of southern Ethiopia on varieties Kulfo and Awassa 83 and compared with two common local planting material conservation methods: leaving “volunteer roots” in the soil which then sprout at the onset of rains; and planting vines under shade or mulch. Across study locations and for both varieties, Triple S resulted in a higher survival rate (81–95%) in storage during the dry season compared to the local conservation methods (7–57%). Plants of both varieties grown from roots conserved with the Triple S method showed significantly higher vine growth and lower weevil and virus infection symptoms compared to plants grown from the two local conservation methods. An additional experiment found that planting at the start of the main rainy season in June and harvesting just before the start of the dry season in October gives the highest number of medium-sized and weevil-free roots suitable for Triple S. The current study demonstrated that the Triple S method is a promising technology for small-scale sweetpotato farmers in dry areas for timely access to high-quality planting material.